Analisis Aspek Mikro Fundamental Terhadap Pola Investasi Bertahap Pada UKM (Transformasi Bertahap dari Ikremental ke Radikal) - Emella Kansa Sulthanah Gumay; Wisnu Yuwono; Erilia Kesumahati (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
Small and Medium Enterprises (SMEs) now mostly rely on digital transformation to stay competitive among technological upheaval. This study intends to investigate the impact of basic micro aspects—including organization, mechanization of information technology (IT) use, simple products, organizational structure, and owner involvement—on the slow investment pattern in the digital transformation of SMEs. Furthermore investigated in this paper is the moderating influence of cognitive response on this link. Data were gathered from 134 SMEs in Batam using a quantitative approach and purposive sampling technique by means of a validated and dependable Likert scale questionnaire and subsequently subjected to partial least squares (PLS) analysis. While direct owner involvement has no appreciable direct influence, the research findings show that organization, IT mechanization, simple products, and organizational structure greatly affect the gradual investment pattern. Nevertheless, the impact of owner involvement and IT mechanization becomes notable when controlled by cognitive reactions, so stressing the relevance of cognitive processes in digitalization decision-making.